The Effect of Remuneration on Employee Job Satisfaction in Government Agencies at the Jayakarta Military Regional Command (Kodam Jaya) - Novingky Ferdinand; Rizky Maulana; Eliza (International Journal of Sharia Business Management, 2022)
In implementing good governance, the civil servant (PNS) factor is an essential factor because it is the central pillar in service to the community to create excellent service. Therefore, one of the factors in creating good civil servants is paying attention to their employees' welfare according to their position. Based on this, a study was conducted to see the effect of remuneration on job satisfaction in Government Agencies at the Jayakarta Military Regional Command. The allowance is expected to increase employee job satisfaction. This research is associative quantitative research, with a significant level of = 0.05 (5%) with a 95% confidence level with a sample of 58 people using a saturated sample. Data collection uses primary data systems, namely observation and questionnaires, and secondary data, namely literature study. Testing the instrument using the validity test, reliability test, and normality test. As for the data analysis method using frequency distribution analysis, simple linear regression, correlation coefficient, coefficient of determination, and t-test. Data calculation is done using SPSS. The results showed that the remuneration in the frequency distribution analysis was perceived as good at 4.12, and employee job satisfaction was quite good at 3.79. In linear regression analysis Y = 39,193 + 0,54X, the correlation coefficient is perceived as strong as 0.611, the coefficient of determination is 37.3%, in the t-test it is perceived that t count > t table is 5.773 > 1.673. then Ho is rejected, and Ha is accepted. So it can be concluded that there is a significant influence between remuneration on employee job satisfaction